Dependence of separately continuous functions on n coordinates on products of compact sets - Mykhailyuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We investigate the problem of the dependence of separately continuous functions on n coordinates on products of spaces each of which is a topological product. In the case where X and Y are products of completely regular countably compact spaces, we establish necessary and sufficient conditions for such a dependence.